Analysis of radioiodine therapy and prognostic factors of differentiated thyroid cancer patients with pulmonary metastasis: An 8-year retrospective study. Issue 19 (May 2017) - Wang, Renfei; Zhang, Yueqian; Tan, Jian; Zhang, Guizhi; Zhang, Ruiguo; Zheng, Wei; He, Yajing
Abstract : Abstract: To assess the efficacy of radioiodine therapy (RIT) and investigate the prognostic factors for patients with pulmonary metastasis secondary to differentiated thyroid carcinoma (DTC) through a retrospective study. A total of 80 patients with radioactive iodine-131 ( 131 I)-avid pulmonary metastasis from DTC treated with 131 I from 2007 to 2014 at our institution entered the study. Treatment response was mainly measured by two parameters: serum thyroglobulin (Tg) levels and post-therapeutic 131 I whole-body scan (WBS). Treatment variables were assessed for statistical significance using the univariate and multivariate analyses. A receiver-operating characteristic (ROC) curve was also plotted to verify the accuracy of predictors. Of these 80 patients, the overall effective rate was 72.5% (58/80), the rates for complete response (CR), partial response (PR), and no response (NR) were 20.0%, 52.5%, and 27.5%, respectively. Univariate analysis showed that gender, pulmonary nodule size, absence or presence of extrapulmonary distant metastases, age, and Tg level at diagnosis were significantly associated with 131 I therapy efficacy. Binary logistic regression analysis revealed that older patients (odds ratio [OR]:1.481, 95% confidence interval [CI]: 1.457–2.091, P  = .020), subjects with higher Tg levels at diagnosis (OR: 1.046, 95% CI: 1.016–1.119, P  = .014), and those with extrapulmonary distant metastases (OR: 1.185, 95%CI: 1.025–1.463, P  = .020) had a higher probability of poor prognosis. The optimal cutoffs for age and Tg level to predict 131 I therapy efficacy for DTC with lung metastases were 46 years old and 55.50 ng/mL, respectively, based on ROC analysis. This study indicated that most DTC patients with pulmonary metastases can obtain partial or complete remission after RIT, while older patients with higher Tg levels at diagnosis and extrapulmonary distant metastases more likely show poor prognosis.